2016
DOI: 10.1128/jvi.02588-15
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Modulates Expression of Noncanonical Wnt Receptor ROR2 To Alter Trophoblast Migration

Abstract: Maternal primary cytomegalovirus (CMV) infection, reactivation, or reinfection with a different viral strain may cause fetal injury and adverse pregnancy outcomes. Increasing evidence indicates that fetal injury results not only from direct viral cytopathic damage to the CMV-infected fetus but also from indirect effects through placental infection and dysfunction. CMV alters Wingless (Wnt) signaling, an essential cellular pathway involved in placentation, as evidenced by reduced transcription of canonical Wnt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 56 publications
(67 reference statements)
1
30
0
Order By: Relevance
“…By dysregulating the physiological condition of the Wnt/β-catenin pathway, HCMV inhibits or severely hampers the processes of cellular replication, movement/migration, and differentiation among others[41,42]. …”
Section: Human Betaherpesvirusmentioning
confidence: 99%
See 1 more Smart Citation
“…By dysregulating the physiological condition of the Wnt/β-catenin pathway, HCMV inhibits or severely hampers the processes of cellular replication, movement/migration, and differentiation among others[41,42]. …”
Section: Human Betaherpesvirusmentioning
confidence: 99%
“…Wnt5a interacts with the tyrosine-like orphan kinase 2 ROR2 and physiologically activates the Wnt/Planar Cell Polarity pathway and Wnt/Ca 2+ pathway[42]. During HCMV infection, infected cells become insensitive to normal Wnt5a ligand signaling but ROR2 expression is significantly increased.…”
Section: Human Betaherpesvirusmentioning
confidence: 99%
“…C-X-C chemokine receptor type 4 (CXCR4)/CXCR7 (9,10) is an important signaling pathway during pregnancy, which is highly expressed in the placenta. It is involved in embryogenesis and implantation of placenta; moreover, they can also form a dipolymer, aggregate β-inhibitory protein and activate its related signaling transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, this could explain the placenta damage and impaired development detected in infections. Moreover, it has also been reported that HCMV infection of trophoblasts can alter signalling pathways, such as Wnt/, expression of adhesion molecules, secretion of cytokines and cellular function, such as migration and invasion (Angelova et al, 2012;Hamilton et al, 2012;Schleiss et al, 2007;van Zuylen et al, 2016;Warner et al, 2012), causing further dysregulation of placenta functions. These changes are linked with higher risks of severe disease in the foetuses and poor pregnancy outcome during the first trimester (Enders et al, 2011;Pass et al, 2006).…”
Section: Congenital Infectionmentioning
confidence: 99%
“…HCMV infection is described to alter the expression of several chemokines Streblow et al, 1999) and chemokines can interfere with cell taxis (e.g., HCMV infection of cytotrophoblasts inhibits CXCL12 expression, which mediates migration of this cell type) (Warner et al, 2012). HCMV infection has also been associated with modulation of canonical and non-canonical Wnt signalling, thereby inhibiting trophoblast migration in response to Wnt ligands (Angelova et al, 2012;van Zuylen et al, 2015). It is possible that several alternative pathways, including those involving the vGPCR, may contribute to modulation of trophoblast migration and that the prevailing effects will depend upon the context of infection, for example differentiation state of the cell.…”
Section: Effects Of Vgpcr In Human Cell Types and Potential Roles Durmentioning
confidence: 99%